Chapter A drone's eye view: A preliminary assessment of the efficiency of drones in mapping shallow-water benthic assemblages - Bellia, Andrea Francesca (Proceedings e report, 2020)
The study assesses consumer drone efficiency for surveying shallow-water benthic cover. We hypothesised that using a drone would reduce duration, and manpower requirements, while increasing accuracy, relative to manual surveys. Results obtained during this study clearly indicated that automated drone surveys were faster and more accurate than manual survey methods under most circumstances. This result has important implications for the scientific and economic aspects of the process and would have a multiplicative effect in monitoring programs that require regular surveys.